Introducing immunotherapy for advanced hepatocellular carcinoma patients: Too early or too fast?. (January 2021) - Lai, Eleonora; Astara, Giorgio; Ziranu, Pina; Pretta, Andrea; Migliari, Marco; Dubois, Marco; Donisi, Clelia; Mariani, Stefano; Liscia, Nicole; Impera, Valentino; Persano, Mara; Tolu, Simona; et al.
Graphical abstract: Highlights: Advanced hepatocellular carcinoma remains a disease with poor prognosis. Immunotherapy is an attractive strategy for advanced hepatocellular carcinoma. Interaction between immunotherapy and tumour microenvironment is crucial. Abstract: Advanced hepatocellular carcinoma (HCC) is the most frequent liver cancer. Immunotherapy has been explored in this disease in order to improve survival outcomes. Nowadays, scientific research is focusing especially on immune checkpoint inhibitors, in particular anti-PD1, anti-PD-L1 and anti-CTLA4 monoclonal antibodies (mAbs), as single-agent or in combination with other immunotherapy agents, target therapies, anti-vascular endothelial growth factor (VEGF) and other agents targeting specific molecular pathways. Other immunotherapy strategies have been assessed or are under investigation in advanced HCC, namely cytokines, adoptive cell therapy, oncolytic virus, cancer vaccines. Each treatment presents specific efficacy and toxicity profiles, strictly related to their mechanism of action and to advanced HCC tumour microenvironment (TME). The aim of this review is to outline the state-of-the-art of immunotherapy in advanced HCC treatment, highlighting data on already investigated treatment strategies, safety and toxicity (including HBV/HCV-related HCC), and ongoing clinical trials focusing on new promising therapeutic weapons.